PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ANTIINFLAMASI KAMAFLAM DI APOTEK KIMIA FARMA MANYAR GRESIK - Hendri Fatriona; Yunus Handoko; Ike Kusdyah Rachmawati (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
Health constitutes a vital aspect of overall well-being and is recognized as a fundamental human right. In the context of contemporary advancements in technology and evolving work demands, there is a notable decline in public awareness regarding healthy lifestyle practices, including insufficient physical activity and the disregard for nutritional values in dietary choices. These trends elevate the risk of both communicable and non-communicable diseases. Established in 1817 by the Dutch East Indies government, Kimia Farma represents Indonesia's pioneering pharmaceutical enterprise. Among its products is Kamaflam, an anti-inflammatory medication produced by PT Kimia Farma, Tbk. Notably, sales of Kamaflam at Pharmacy Kimia Farma Manyar Gresik in September surpassed those of several competing products, influenced by a variety of factors. Consequently, this study aims to analyze the effects of brand image, product quality, and personal selling on the purchasing decisions associated with Kamaflam at Pharmacy Kimia Farma Manyar Gresik. Conducted in Gresik, data were gathered via questionnaires distributed to individuals who had purchased the product between October and November. Through purposive sampling, a sample of 50 respondents was selected. The data further analyzed through multiple linear regression using SPSS 26.0. The analysis revealed that brand image, product quality, and personal selling each have a significant impact on purchasing decisions, both partially and simultaneously.